Gender-based violence in confined women during the SARS-CoV-2 pandemic - Torres-Velasco, Diana Patricia; Salas-Cortez, Beatriz; Martínez-Basilio, Dulce Giseli; Mejía-Cervantes, Rosa; Vásquez-Martínez, Josué; Zacarías-Martínez, Monserrat (Horizonte Sanitario, 2022)
Objective: To identify the presence of gender-based violence in women confined dueto the Covid-19 pandemic in the Oaxaca Coast Region.Materials and methods: Quantitative, descriptive, correlational and cross-sectionalresearch in 50 women over 18 years of age who remained at least 1 month in confinementdue to the Covid-19 pandemic, who applied a questionnaire using the Intimate PartnerViolence Severity Index, respecting the pertinent ethical recommendations of theGeneral Health Law on Health Research. The data were processed in the SPSS version21 statistical program and descriptive statistics and Pearson´s correlation coefficientwere used.Results: A prevalence of psychological violence was found to be 90%. 72% ofthe women reported physical violence and 64% were victims of sexual violence. Apositive correlation was observed between age and physical violence (r= 0.405, p=0.004), psychological violence (r= 0.416, p= 0.003) and sexual violence (r= 0.527, p=0.000); a negative correlation was observed in the variables schooling and physicalviolence (r= -0.538, p= 0.000), psychological violence (r= -0.488, p= 0.000), sexualviolence (r= -0.411, p= 0.003).Conclusions: Gender-based violence is an issue that has taken great relevancein recent years, and that currently continues to be of concern. Despite the fact thatinformation has been disseminated, violence continues to exist within mexican homes.In the Oaxaca Coast during the confinement by Covid-19, gender-based violence hasbeen highly prevalent, which is why it is necessary to implement measures to preventand treat gender-based violence.Keywords: Gender-based violence; Confinement; Women.